Drainage Construction as an Effort to Improve Public Health through Community Service in the Griya Permata Complex, Banjarmasin - Effendie, Faryanto; Fakhrurrazi; Khaliq, Abdul (PT FORMOSA CENDEKIA GLOBAL, 2025)
Residential development in the Griya Permata Complex has reduced water catchment areas, resulting in chronic flooding that has the potential to cause public health problems, such as the spread of mosquito-borne diseases. This community service project aims to address this problem through the construction of a water channel. The methods used included land clearing, bowplank measurements, and manual channel excavation by a team from Banjarmasin State Polytechnic and students. To date, the work has reached 70% completion, with an excavation volume of 72 m³. The results show that the water channel construction can accommodate flooding and reduce runoff, demonstrating that simple interventions can improve environmental quality and public health